The Role of Video Content in Shaping Public Perception of King Abdullah II's Speech at the European Parliament: A Comparative Study of Jordanian and International Digital News Platforms - Kreishan, Asem (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Political speeches are essential for motivating, comforting, and unifying individuals. This study analyzes King Abdullah II's address to the European Parliament through the lenses of pragmatics and speech theory. This research examines the rhetorical methods and diction employed in King Abdullah's address to effectively convey his themes, advocating for global solidarity and collective action to halt the war in Gaza, as well as his vision for the future of regional conflicts. Information was sourced from the official website of King Abdullah II of Jordan. The findings demonstrate the speech's effectiveness in achieving its communication objectives and its ability to influence public opinion. The speech employs pragmatic components, including allusion, strategic tact, context, metaphor, expression, and assumption. The rhetorical analysis framework used demonstrates how speeches construct narratives that connect with the European Parliament and foster public involvement in concluding the conflict in Gaza. The research highlights the significant role of language in political discourse, influencing conflicts and their impact on the political landscape in Jordan and the Middle East.